2021
DOI: 10.1002/jca.21931
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic plasma exchange in patients with severe obesity (BMI >40): A survey of practices in the United States

Abstract: Background: The prevalence of obesity in the United States is estimated at 42.4% and expected to increase over the next decade. Therefore, understanding how to best perform certain medical procedures on severely obese (SO) patients is a necessity. This study presents results on the current methods of performing therapeutic plasma exchange (TPE) on SO patients. This paper aims to contribute to the existing literature by providing new insights into calculating plasma volume (PV) for TPE in SO patients.Methods: B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Of the 96 TPE procedures performed, it was found that at the beginning of TPE procedure, there were about 52 cases (54.3%) of hypotension, but after fluid management was given, hypotension could be managed in less than 15 minutes and there was only 1 incident (1%) of untreated hypotension complications. The patient with the hypotension had BMI value of 32 kg/m 2 that according to a previous study in America in 2021, there were difficulties in calculating replacement fluids for obese patients so they conduct a greater risk of hypotension (Babariya et al, 2021). In the GBS group, most complications were of electrolyte disturbances.…”
Section: Discussionmentioning
confidence: 96%
“…Of the 96 TPE procedures performed, it was found that at the beginning of TPE procedure, there were about 52 cases (54.3%) of hypotension, but after fluid management was given, hypotension could be managed in less than 15 minutes and there was only 1 incident (1%) of untreated hypotension complications. The patient with the hypotension had BMI value of 32 kg/m 2 that according to a previous study in America in 2021, there were difficulties in calculating replacement fluids for obese patients so they conduct a greater risk of hypotension (Babariya et al, 2021). In the GBS group, most complications were of electrolyte disturbances.…”
Section: Discussionmentioning
confidence: 96%
“…Dear Editor, A recent publication by Babariya et al 1 in the Journal of Clinical Apheresis described the survey results of the current practices for total blood volume (TBV) calculations for high-BMI patients among 45 academic institutions in the United States. The authors of that publication focused on TBV estimation in severely obese patients with a body mass index (BMI) of over 40 undergoing therapeutic plasma exchange procedures (TPE).…”
mentioning
confidence: 99%